The effect of neurosphere culture conditions on the cellular metabolism of glioma cells - Kahlert, Ulf Dietrich; Koch, Katharina; Suwala, Abigail Kora; Hartmann, Rudolf; Cheng, Menglin; Maciaczyk, Donata; Willbold, Dieter; Eberhart, Charles G.; Glunde, Kristine; Maciaczyk, Jarek (Folia Neuropathologica, 2015)
Malignant gliomas, with an average survival time of 16-19 months after initial diagnosis, account for one of the most lethal tumours overall. Current standards in patient care provide only unsatisfying strategies in diagnostic and treatment for high-grade gliomas. Here we describe metabolic phenomena in the choline and glycine network associated with stem cell culture conditions in the classical glioma cell line U87. Using high-resolution proton magnetic resonance spectroscopy of cell culture metabolic extracts we compare the metabolic composition of U87 chronically propagated as adherent culture in medium supplemented with serum to serum-free neurosphere growth. We found that the switch to neurosphere growth, besides the increase of cells expressing the putative glioma stem cell marker CD133, modulated a number of intracellular metabolites including choline, creatine, glycine, and myo-inositol that have been previously reported as potential diagnostic markers in various tumours. These findings highlight the critical influence of culture conditions on glioma cell metabolism, and therefore particular caution should be drawn to the use of in vitro system research in order to investigate cancer metabolism.